Standing asymmetry and functional ability in relation to gait parameters in hemiparetic stroke patients (2006)
Objective: Relationships between some temporospatial gait parameters and each of functional ability and standing asymmetry (measured as asymmetry ratio) in hemiparetic stroke patients were investigated. Design: Ex-post facto research design. Sample Size: Thirty-one (18 males and 13 females) patients with hemiparesis, aged between 35 and 65 years (56.97 ± 11.53) were consecutively recruited from the physiotherapy out-patient facility of a Nigerian teaching hospital. Measurements: Two weighing scales were used to measure relative standing weight distribution on each lower limb and subsequently converted to asymmetry ratio (AR), while functional ability was determined using the modified motor assessment scale. Gait parameters were assessed using foot print analysis, obtained during a 10-metre walk test. Pearson's correlation matrix (r) was calculated to establish relationship at 0.05 alpha. Results: Results showed a significantly negative correlation between asymmetry ratio and each of stride length, step length and functional ability (p<0.05). Significantly positive correlation was found between motor function and cach of stride length, step length, cadence, walking speed and step time (p<0.05) were obtained. Conclusion: The lesser the standing asymmetry in stroke patients, the better their motor functions and gait performance. Programmes aimed at enhancing weight bearing activities through the paretic lower limb, to attain standing symmetry, may be used to enhance functional ability and produce better gait functions in post-stroke patients.